Susceptibility to Plasmodium falciparum Malaria: Influence of Combined Polymorphisms of IgG3 Gm Allotypes and Fc Gamma Receptors IIA, IIIA, and IIIB - Fall, Abdou Khadre Dit Jadir; Dechavanne, Celia; Sabbagh, Audrey; Guitard, Evelyne; Milet, Jacqueline; Garcia, André; Dugoujon, Jean-Michel; Courtin, David; Migot-Nabias, Florence (Frontiers in Immunology, 2020)
The binding of immunoglobulin (Ig) to Fc gamma receptors (FcgR) at the immune cell surface is an important step to initiate immunological defense against malaria. However, polymorphisms in receptors and/or constant regions of the IgG heavy chains may modulate this binding. Here, we investigated whether polymorphisms located in FcgR and constant regions of the heavy chain of IgG are associated with susceptibility to P. falciparum malaria. For this purpose, a clinical and parasitological follow-up on malaria was conducted among 656 infants in southern Benin. G3m allotypes (from total IgG3) were determined by a serological method of hemagglutination inhibition. FcgRIIA 131R/H and FcgRIIIA 176F/V genotypes were determined using the TaqMan method and FcgRIIIB NA1/NA2 genotypes were assessed by polymerase chain reaction using allele-specific primers. Association analyses between the number of malaria infections during the follow-up and polymorphisms in IgG G3m allotypes and FcgR were studied independently by zero inflated binomial negative regression. The influence of combinations of G3m allotypes and FcgRIIA/FcgRIIIA/FcgRIIIB polymorphisms on the number of P. falciparum infections, and their potential interaction with environmental exposure to malaria was assessed by using the generalized multifactor dimensionality reduction (GMDR) method. Results showed that individual carriage of G3m24 single allotype and of G3m5,6,10,11,13,14,24 phenotype was independently associated with a high risk of malaria infection. A risk effect for G3m6 was observed only under high environmental exposure. FcgRIIIA 176VV single genotype and combined carriage of FcgRIIA 131RH/FcgRIIIA 176VV/FcgRIIIB NA1NA2, FcgRIIA 131RR/FcgRIIIA 176FF/FcgRIIIB NA1NA1, FcgRIIA 131RR/FcgRIIIA 176VV/FcgRIIIB NA2NA2 and FcgRIIA 131RR/FcgRIIIA 176VV/FcgRIIIB NA1NA2 genotypes were related to a high number of malaria infections. The risk was accentuated for FcgRIIIA 176VV when considering the influence of environmental exposure to malaria. Finally, the GMDR analysis including environmental exposure showed strengthened associations with a malaria risk when FcgRIIA/FcgRIIIA/FcgRIIIB genotypes were combined to G3m5,6,11,24 and G3m5,6,10,11,13,15,24 phenotypes or G3m10 and G3m13 single allotypes. Our results highlight the relevance of studying IgG heavy chain and FcgR polymorphisms, independently as well as in combination, in relation to the individual susceptibility to P. falciparum infection. The intensity of individual exposure to mosquito bites was demonstrated to impact the relationships found.